Developing E-Modules Based of SSI the Theme of Biodiversity to Enhance Students’ Critical Thinking Skills Abilities - Nuryunita Dewantari; Zuida Ratih Hendrastuti; Laura Ardiyani Rohmah Cahyani; Nurul Rahmawati (Jurnal Penelitian Pendidikan IPA, 2026)
Critical thinking skills are one of the important skills to be applied in science learning. Critical thinking skills refer to students abilities to analyze complex issues, investigate questions that lack clear answers, evaluate various perspectives from information sources, and draw accurate conclusions. Several previous studies have shown that students' critical thinking skills in Indonesia are still relatively low and need to be improved. One approach is to use e-modules based SSI (socio scientific issues on the topic of biodiversity. E-modules are electronic teaching materials containing learning materials that students can use independently. Socio-scientific issues are social problems related to science. Biodiversity is one of the topics taught in junior high school science. E-modules based SSI on the theme biodiversity is an electronic module that presents social science issues related to the theme of biodiversity which is able to train students' critical thinking skills. This study aims are (1) to determine eligibility of e-modules based SSI on the topic biodiversity for improving the students critical thinking skills and to determine; (2) to determine the level of practicality of the e-modules based SSI on the topic biodiversity for improving the students critical thinking skills; and (3) to determine the effectiveness of e-modules based SSI on the topic biodiversity for improving the students critical thinking skills. The research employed a development method using the ADDIE development model are Analysis, Design, Development, Implementation, and Evaluation. The developed e-modules has been validated by experts and field testing in junior high school students in Magelang city. Based on the validator's assessment, the total score from four validator was 15.71 with an average score of 3.92, indicating that the developed e-module based SSI is good and suitable for use in science learning. Then, from the results of the student response questionnaire, the overall average score for the material, language, presentation, and graphics aspects was 4.133 with a good category, so that e-module based SSI is suitable for use in science learning. Based on the result of the paired sample t-test with a Sig. 0.000 < 0.05 and an N-gain value of 0.34, categorized as currently, so that the e-module is effective in improving critical thinking skills. The conclusion of this study is that the developing e-module is suitable, deemed practical, effective for use science learning in junior high school.